The development of a neural network model for the structural improvement of perovskite solar cells using an evolutionary particle swarm optimization algorithm - Ghalambaz, Nasim; Ganji, Jabbar; Shabani, Pejman (Journal of computational electronics, 2021)
The revolution represented by third-generation photovoltaic devices relied on the discovery of various hybrid organic–inorganic perovskite materials to convert solar into electrical energy. One of the advantages of such cells is their low cost due to the raw materials and cheap production methods used. Nevertheless, these cells face several challenges, such as inadequate stability and the hysteresis phenomenon. To overcome these, perovskite solar cell (PSCs) with planar and inverted structures have been utilized with an inorganic hole transport layer (HTL), achieving acceptable efficiency. As there is no closed-form system of equations to describe the operation of such cells, neural networks have been employed for their modeling. In optimization algorithms, the values of the parameters must be swept, since most current simulation tools cannot use them directly. Such software optimization can notably decrease the cost of cell design. This paper presents a practical way to achieve the mentioned aim. In particular, an artificial neural network (ANN) is exploited for the modeling, then an evolutionary particle swarm optimization (E-PSO) algorithm is developed to optimize the structure to achieve the highest efficiency based on searching the energy conversion. The results of the simulations are then employed in SCAPS software to train the neural network. This optimization leads to the achievement of an efficiency of 23.76% for the proposed structure, better than values reported in literature.